Does hydroxychloroquine reduce the risk of infection in patients with systemic lupus erythematosus? a systematic review and meta-analysis - Shangtian Wang; Maojia Ka; Wenying Wu (PLoS ONE, 2025)
Objectives This study aimed to investigate the anti-infective utility of hydroxychloroquine in patients with systemic lupus erythematosus (SLE) by analyzing published case-control and cohort studies. Methods A systematic literature review was conducted on January 28, 2024, using PubMed, Cochrane, Embase, and Web of Science Core Collection databases. Odds ratios (OR) were used for statistical analysis. Results Hydroxychloroquine exhibits a propensity to diminish infection risk in systemic lupus erythematosus patients, albeit without statistical significance (OR = 0.77, 95%CI 0.51-1.18, p = 0.23). Subgroup analyses revealed a significant prevention of serious infections (OR = 0.40, 95%CI 0.25-0.64, p = 0.0001). Interestingly, a potential causal relationship between hydroxychloroquine use and lower infection risk was observed in the cohort studies subgroup (OR = 0.66, 95%CI 0.44-0.99, p = 0.04), but not in the case-control studies subgroup (OR = 1.06, 95%CI 0.63-1.79, p = 0.83). It is important to note the risks associated with high-dose use, such as retinopathy. Conclusions Although hydroxychloroquine tends to reduce infection risk in SLE patients, the evidence is not strong. It can decrease severe infections, but high doses should be used cautiously and selectively in patients with impaired renal function. Further studies are required to establish optimal dosing and efficacy for specific diseases, considering the potential influence of study design on the observed associations between hydroxychloroquine use and infection risk in SLE patients.